2021
DOI: 10.3390/ijerph18147612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1 Year of Lifestyle Intervention on Institutionalized Older Adults

Abstract: The socio-economic and health consequences of our ageing population are well documented, with older adults living in long-term care facilities amongst the frailest possessing specific and significant healthcare and social care needs. These needs may be exacerbated through the sedentary behaviour which is prevalent within care home settings. Reducing sedentary time can reduce the risk of many diseases and improve functional health, implying that improvements in health may be gained by simply helping older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…PA/exercise might be a way to improve the gut microbiome during ageing since it influences several organs, cells, and tissues, and involves several molecular pathways. Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…PA/exercise might be a way to improve the gut microbiome during ageing since it influences several organs, cells, and tissues, and involves several molecular pathways. Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The first assumption is that gym users represent an active and health-oriented subset of the general population leading to beneficial adaptations on CV risk factors. Even when compared in terms of age and gender, gyms are frequented by a selected active population, which therefore cares more about health issues, treats risk factors more carefully and generally recognizes a preventive and therapeutic role of PA and exercise [ 31 , 32 ]. The intrinsic role of regularly performed PA that has a strong impact on reducing all CV risk factors should be added to this fact.…”
Section: Discussionmentioning
confidence: 99%
“…43 In another study, participants in a 1-year intervention showed a reduction in symptoms of depression and an improvement in balance, upper limb strength, and basic ADLs compared with the control group. 47 Finally, 12 weeks of daily supervised, individualized training improved balance, physical activity levels, and transfers in LTC residents compared with the control group. 40 However, it is important to mention that one of the main barriers to implementing a daily exercise intervention in LTC is a lack of support and staff.…”
Section: Combined Physical Activitymentioning
confidence: 94%